2018
DOI: 10.5588/ijtld.18.0073
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the QuantiFERON®-TB Gold In-Tube assay in tuberculin skin test converters: a prospective cohort study

Abstract: Concordance between TST and QFT-GIT was moderate among TST converters in this urban African population. These findings call for improved tests that more accurately measure conversion to tuberculous infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Although BCG is known to produce false positive TST results, the effect is minimal after 10 years of age [ 26 ]. Further, 75% of HHCs had TST ≥ 10 mm compared with 53% of IGRA ≥ 0.35 UI/ml which is consistent with other household contact studies in developing countries whereas TST often yields more positive results compared with IGRA [ 27 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although BCG is known to produce false positive TST results, the effect is minimal after 10 years of age [ 26 ]. Further, 75% of HHCs had TST ≥ 10 mm compared with 53% of IGRA ≥ 0.35 UI/ml which is consistent with other household contact studies in developing countries whereas TST often yields more positive results compared with IGRA [ 27 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, excessive dehydration impairs water absorption due to intestinal mucosal atrophy, leading to massive intestinal liquid retention, as shown in Figure 1. One report has described similar abdominal CT findings from a patient with haemorrhagic shock, 4 indicating that hypovolemia is one of the main causes of intestinal ischaemia that leads to impaired water absorption. In conclusion, paediatricians should advice sports coaches and school teachers about the appropriate timing of oral rehydration: before manifestation of intestinal ischemic symptoms such as vomiting or diarrhoea.…”
Section: Massive Intestinal Liquid Retention In a Case Of Severe Heatmentioning
confidence: 86%
“…TST and IGRA are both imperfect screening tests for TB infection, and there is compelling evidence for the limited sensitivity of IGRA in both active TB disease and latent TB infection (LTBI). 4 The limitations of IGRA are particularly relevant for infants and young children, 5 and national and international guidelines therefore continue to advise the use of TST in preference to IGRA for screening children under 5 years of age. 6 Discordant results in this age group, especially those children who have received BCG at birth, is especially problematic given that they will potentially benefit the most from preventive therapy as they have the highest risk to progress to active TB disease.…”
Section: Dear Editor Interpretation and Management Of Discordant Tubmentioning
confidence: 99%
“…In high‐burden settings and areas in which BCG vaccination is ubiquitous, the accuracy of the tuberculin skin test for the diagnosis of tuberculosis infection is controversial . TST and QFT test concordance test was poor, which was same as other regions with highest TB burden, where BCG are administered . In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent.…”
Section: Discussionmentioning
confidence: 97%
“…21,28 TST and QFT test concordance test was poor, which was same as other regions with highest TB burden, where BCG are administered. [29][30][31][32][33][34] In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent. In prior work from our province, we have shown that the prevalence of nontuberculous Mycobacterium is high.…”
Section: Discussionmentioning
confidence: 99%